Determinants of Employee Performance: Overview of Aspects of Communication, Work Stress and Compensation - Sutrisno Sutrisno (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to analyze the determinants of performance in terms of communication, work stress and compensation for college employees in Jakarta, the sample of this study is permanent employees not lecturers at private campuses in Jakarta. The method used is quantitative. The data collection technique used purposive sampling, where the respondents' criteria were permanent campus employees with a minimum of 2 years of service, questionnaires were distributed to 100 respondents, but only 85 questionnaires were complete and could be processed further. Distribution of questionnaires through google form during January to March 2022. The data analysis technique used is multiple linear regression by performing linearity test, normality test, assumption test classical, and hypothesis testing to test the significance of the effect together with the level of 5% significance. The results of this study indicate that partially and simultaneously Communication, Job Stress, and Compensation are determinant factors that have a significant effect on the performance of permanent employees at private campuses in Jakarta.